2015
DOI: 10.1016/j.ijgo.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral contraceptive use and markers of iron deficiency in a cross‐sectional study of Tanzanian women

Abstract: The significant association between OC use and iron status has important implications for educating healthcare providers and women about additional nutritional benefits of the use of OCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Another study conducted amongst women aged 15─49 years in Tanzania also found that oral contraceptive use was inversely associated with markers of iron status. 24 The current study did not find a significant association between contraceptive use and haemoglobin levels.…”
Section: Discussioncontrasting
confidence: 77%
“…Another study conducted amongst women aged 15─49 years in Tanzania also found that oral contraceptive use was inversely associated with markers of iron status. 24 The current study did not find a significant association between contraceptive use and haemoglobin levels.…”
Section: Discussioncontrasting
confidence: 77%
“…Consistent with these findings, a significant negative association was found between anemia and hormonal contraceptive use [17, 29], suggesting the potential protective effect of hormonal contraceptives against anemia. Reduction in menstrual bleeding associated with the use of hormonal contraceptives could be the plausible underlying mechanism [50]. Evidence of non-contraceptive benefits of hormonal and IUD contraceptive methods against menstrual blood flow and other women’s problems such as endometriosis, endometrial cancer, ovarian cancer, colorectal cancer, ectopic pregnancy, and pre-menstrual dysphoric disorder has been documented in the literature [51].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by a study conducted in Rwanda [ 22 ]. This could be justified by the protective effects of modern contraceptives on menstrual bleeding, pregnancy and birth-related hemorrhages [ 23 ]. Concurrent iron supplementation is also available particularly for those women who have used oral contraceptives, which is very important for the prevention of anemia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%